Logistics Outsourcing and Procurement Performance in Local Governments: Case of Mbale District Local Government - Ronald Owor (Uganda Christian University, 2024)
The research was undertaken to investigate on logistics outsourcing and procurement performance in Mbale district local government. It was guided by three objectives; to find out the effect of technological advancements on procurement performance of Mbale district local government, to assess the effect of risk management on procurement performance of Mbale district local government, to analyze the effect of regulatory compliance on procurement performance of Mbale district local government. The research study used a sample size of 45 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective shows that technological advancements positively (Beta=0.153) predicts the procurement performance of Mbale district local government and effect is significant at p-value < 0.05. by 9.6%, Results of the second objective reveals that risk management positively (Beta=0.224) predicts the procurement performance of Mbale district local government and effect is significant at p-value < 0.05 by 7.7% while results of the third objective show regulatory compliance (Beta=0.091) predicts and affects their procurement performance of Mbale district local government. However, its effect is insignificant at p-value > 0.05 by 2.1%. It can be concluded that risk technological advancements has a significant effect on procurement performance of Mbale district local government, risk management has a significant effect on procurement performance of Mbale district local government council and lastly regulatory compliance has a significant effect on procurement performance of Mbale district local government. There is need for government to integrate advanced digital tools and platforms that streamline procurement processes. This includes adopting e-procurement systems to automate and standardize purchasing activities, using data analytics for informed decision-making, and implementing block-chain technology to ensure transparency and traceability in the supply chain.
Undergraduate Research